Synthetic impulse and aperture radar (SIAR) a novel multi-frequency MIMO radar - Chen, Baixiao; Wu, Jianqi (John Wiley & Sons Singapore Pte. Ltd., 2014)
Discusses the operating principle, signal processing method, target measurement technology, and experimental results of a new kind of radar called synthetic impulse and aperture radar (SIAR). This book aims to help readers acquire an insight into the concept and principle of the SIAR.